(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2019)
This study aimed to find out the effect of different copies of the book on the understanding of the words of Sibawayh, through one of his explanations, which is to explain Abu Nasr Al- Qurtubi named explain the eyes of Sibawayh book, and compare with other explanations, and copies of the book printed, as the study aimed to achieve the date of his birth, and a statement of his works The study reached an estimate of the approximate date of the birth of Abu Nasr Al- Qurtubi, to reveal his copy of the book, and to mention his version of the book of Sibawayh.The study also found the effect of different copies of the book in understanding Sibawayh’s words.